KERASULAN AWAM DI BIDANG POLITIK (SOSIAL-KEMASYARAKATAN), DAN RELEVANSINYA BAGI MULTIKULTURALISME INDONESIA - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2017)
The political responsibility is important, not because of the need for the love of the homeland and the challenge of the disintegration of the nation in multicultural sphere, but must be born of deep Christian faith. This paper specifically addresses to the lay apostolate in socio-politics-society. The Catholic laity was also called to be salt and light in the political world. The emergence of some form of practical theology (such as liberation theology and political theology) affirms that concern. The theme of the laity will be juxtaposed with a review of the "political attitude" voiced by the prophets in Scripture. The hope is that the laity will become more aware of its social-political calling as part of the faithful life to sound prophetic voice in the world. The struggle of the Church into a prophetic power largely depends on the laity (and of course in good cooperation with the priests). The laity today are called to be new prophets to proclaim the truth without becoming part of the defilement itself